Cadastro Geotécnico dos solos finos lateríticos para fins de pavimentação no município de Goiânia- GO - CARDOSO, Ricardo Alves (2010)
This work aims at the register of geotechnical areas in Goiania-GO, showing the occurrence of fine lateritic soils with potential for use in flooring. The methodology is based on work developed by Nogami and Villibor (1995). From surveys and collecting 17 samples in field tests were conducted from MCT (Mini-MCV, Loss of mass by immersion, compression and Mini-CBR) and verified the mechanical and hydraulic properties of these soils. The samples were collected at sites previously chosen using as reference the pedological map of Goiania, trying to distribute them to all soil units of this map. The surveys were performed to a depth of 2 m in each hole the soils were mixed, representing what occurs in practice during the operation of a loan area. The samples collected for the study were those who had only fine soil grains with diameters of less than 2 mm (sieve nº. 10). Tests were also carried out conventional characterization (particle size, Atterberg limits and specific gravity) of the samples collected to better identify these soils. The results obtained with all samples have the intention to form a database for future research in the area of pavement. It was found that in Goiania most soils are lateritic clay and can be applied in the construction of paviments with low traffic volume.